2019
DOI: 10.1088/1361-6579/ab4b13
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the fetal electrocardiogram for morphological analysis from two trans-abdominal channels via optimal shrinkage

Abstract: We propose a novel algorithm to recover fetal electrocardiogram (ECG) for both the fetal heart rate analysis and morphological analysis of its waveform from two or three trans-abdominal maternal ECG channels. We design an algorithm based on the optimal-shrinkage under the wave-shape manifold model. For the fetal heart rate analysis, the algorithm is evaluated on publicly available database, 2013 PhyioNet/Computing in Cardiology Challenge, set A (CinC2013). For the morphological analysis, we analyze CinC2013 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…• In [45], optimal shrinkage was used to determine fHR with accuracy of 79.25±31.75% for (semi)-real records and with 93.21 ± 14.31% for synthetic records. In both cases, these are worse results than we have achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• In [45], optimal shrinkage was used to determine fHR with accuracy of 79.25±31.75% for (semi)-real records and with 93.21 ± 14.31% for synthetic records. In both cases, these are worse results than we have achieved.…”
Section: Discussionmentioning
confidence: 99%
“…• The authors of [45] used an algorithm based on the optimal-shrinkage under the wave-shape manifold model to extract fECG. Both fHR and signal morphology (PR, QT and ST intervals) were analyzed during the experiments on a dataset including real and simulated signals indicating the physiological and pathological condition of fetuses (e.g.…”
Section: A Morphological Analysismentioning
confidence: 99%
“…In our previous work, the effects of noise robustness and morphology recovery by optimal shrinkage and other template estimation algorithms had been compared for the purpose of extracting fetal ECG from the trans-abdominal maternal ECG [27] over the Physionet CinC Challenge 2013 database [39]. These methods included independent component analysis (ICA), principal component analysis (PCA), least mean square (LMS), recursive least square (RLS), echo state neural network (ESN), and extended Kalman filter (EKF).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we applied a recently developed denoise technique called optimal shrinkage (OS) [26]. In our previous publication [27], we have demonstrated that a better and more adaptive template for each cardiac cycle is obtained through OS, which helps recover ECG morphology from noisy signals. However, we observed a morphology distortion after the application of OS on clean signals, where "clean" means the noise is dominated by the beat to beat variation.…”
Section: Introductionmentioning
confidence: 99%
“…r Number of Input Channels Su et al [84] introduced a very promising single channel blind source separation (scBSS) algorithm. The algorithm contained three steps.…”
Section: R Thresholding Rules and Parametersmentioning
confidence: 99%